1992
DOI: 10.1007/bf00318653
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the glyoxysomal isocitrate lyase genes of Aspergillus nidulans (acuD) and Neurospora crassa (acu-3)

Abstract: The nucleotide sequences of the genes encoding the acetate-inducible glyoxylate cycle enzyme isocitrate lyase from the ascomycete fungi Aspergillus nidulans (acuD) and Neurospora crassa (acu-3) are presented. The respective A. nidulans and N. crassa genes are interrupted at identical positions by two introns and encode proteins of 538 and 543 amino acids, which have 75% identity. The predicted protein sequences do not demonstrate the C-terminal tripeptide S-K-L that has been implicated in peroxisomal targeting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

1993
1993
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 31 publications
1
30
0
Order By: Relevance
“…The comparison of the deduced ICL protein sequence from E. coli with those from eucaryotic organisms revealed a high level of similarity between the E. coli and the eucaryotic enzymes. However, the E. coli enzyme turned out to be about 16 kDa smaller than those from eucaryotes (33). This result is in agreement with the findings that by sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) analysis, most ICLs from eucaryotes are significantly larger than their procaryotic counterparts (for a review, see reference 46).…”
supporting
confidence: 87%
“…The comparison of the deduced ICL protein sequence from E. coli with those from eucaryotic organisms revealed a high level of similarity between the E. coli and the eucaryotic enzymes. However, the E. coli enzyme turned out to be about 16 kDa smaller than those from eucaryotes (33). This result is in agreement with the findings that by sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) analysis, most ICLs from eucaryotes are significantly larger than their procaryotic counterparts (for a review, see reference 46).…”
supporting
confidence: 87%
“…The carboxy-terminal sequence of isocitrate lyase from P. pastoris does not coincide with the eukaryotic signal S(A,C)-K(H,R)-L for import of the protein into the peroxisome. However, peroxisomal Icl from Aspergillus nidulans and Neurospora crassa lack the PTS1-like carboxy-terminal amino acids S(A,C)-K(H,R)-L (Gainey et al, 1992). Therefore, conclusive evidence for the localization of the enzyme in P. pastoris can only be obtained from further analysis.…”
Section: Resultsmentioning
confidence: 99%
“…By analogy with acu-D, the ICLs of A. nidulans (Gainey et al, 1992), D111, D165, D167 and E194 are suggested to be a cluster for the Mg 2+ -binding site. The predicted amino acid sequence was compared with those of the ICLs of Phanerochaete chrysosporium, C. cinereus (Chaure et al, 1997), A. nidulans (Gainey et al, 1992) and Saccharomyces cerevisiae (Schöler & Schüller, 1993), which revealed 83, 79, 63 and 54 % identity, respectively (Fig. 1).…”
Section: Characterization Of Fpicl1mentioning
confidence: 99%